Hannibal - Harris, Thomas (William Heinemann, 1999)
HANNIBAL LECTER HAS BEEN ON THE RUN FOR SEVEN YEARS. And seven years after he helped FBI Special Agent Clarice Starling bring down Buffalo Bill, her career is collapsing after a disastrous drug bust. Meanwhile, seven years after violently escaping from custody, Hannibal Lecter is hunted by Mason Verger, a psychopathic former client obsessed with feeding him to wild boars. With the one-time partners at a low ebb, Hannibal is the one to reach out to Clarice, who has been plagued by dreams of his rasping voice. It has been seven years since they both came to realise they shared more than they expected. Seven years since their last meeting. Seven years to lay plans for the next one. Thomas Harris takes us once again into the mind of a killer, crafting a chilling portrait of insidiously evolving evil - a tour de force of psychological suspense. Seven years have passed since Dr. Hannibal Lecter escaped from custody, seven years since FBI Special Agent Clarice Starling interviewed him in a maximum security hospital for the criminally insane. The doctor is still at large, pursuing his own ineffable interests, savoring the scents, the essences of an unguarded world. But Starling has never forgotten her encounters with Dr. Lecter, and the metallic rasp of his seldom-used voice still sounds in her dreams. FBI agent Clarice Starling's involvement in a dramatic drug bust brings her once again to the attention of cannibal killer Dr. Hannibal Lecter who escaped from custody seven years earlier after helping Clarice nab a serial murderer. Mason Verger remembers Dr. Lecter, too, and is obsessed with revenge. He was Dr. Lecter's sixth victim, and he has survived to rule his own butcher's empire. From his respirator, Verger monitors every twitch in his worldwide web. Soon he sees that to draw the doctor, he must have the most exquisite and innocent-appearing batt; he must have what Dr. Lecter likes best.